Faktor yang Berdampak terhadap Kinerja Guru MAN di Kota Rembang - Ardhanari, Aria Anggira; Tahwin, Muhammad (Universitas Batanghari, 2024)
The motive of this observe is to expose the impact of labor subject, organizational lifestyle and motivation at the performance of instructors in Madrasah Aliyah Negeri 1 Rembang. the academics of Madrasah Aliyah Negeri 1 Rembang have been used on this observe. A sample of 50 instructors changed into used on this study. statistics analysis strategies the usage of multiple linear regression analysis. The results confirmed that work discipline and motivation had a substantial nice effect on instructor overall performance in Madrasah Aliyah Negerti 1 Rembang, and organizational lifestyle had a negative and insignificant impact on instructor overall performance in Madrasah Aliyah Negerti 1 Rembang. The adjusted R-squared value is 0.534. as a result, it may be interpreted that 53.4% of teaching and work results can be defined by means of 3 independent variables, which are work discipline, organizational subculture and motivation. The final 46.6% may be defined by using different variables not investigated on this observe.